The Effect of Employee Development on Work Quality Mediated by Employee Work Effectiveness at Office of the Mayor of Binjai - Irwansyah Irwansyah; Mesra B (International Journal of Economics, Management and Accounting (IJEMA), 2023)
The aims of this research were to analyze and investigate the role of employee performance effectiveness in mediating the relationship between employee development and employee performance quality at the mayor office of Binjai. The type of research in this study was quantitative associative. The research was conducted at the Mayor Office of Binjai. The population in this study consisted of 100 employees. The sampling technique used was saturated sampling, where the entire population was taken as the sample. The data collection technique used was through distributing questionnaires. The data analysis in this study was carried out using Smart PLS 3.0 with path analysis model. The results of this research indicated that (1) Employee development had a direct and significant effect on the quality of employee performance at the Major Office of Binjai; (2) Employee development has a direct and significant effect on employee effectiveness at the Mayor Office of Binjai; (3) Employee performance effectiveness had a direct and significant effect on the quality of employee performance at Mayor Office of Binjai; (4) The variable of work effectiveness could indirectly mediate the influence of employee development on the quality of employee performance at the Major Office of Binjai.